A corrosion study on W-Cu alloys in sodium chloride solution at different pH. (20th February 2021) - Guo, Dawei; Kwok, Chi Tat
Abstract: A corrosion study of two types of tungsten-copper (W-Cu) alloys in 3.38 wt.% NaCl solution with different pH at 25 °C were investigated using potentiodynamic polarization and immersion test. It is crucial that the corrosion behavior and preferential attacked phases of the W-Cu alloys were found to alter with pH. The micro-galvanic effect of tungsten phase and copper binder played a significant role. It was also proved that the existence of aggressive chloride ions could accelerate the Cu binder dissolution in acidic and neutral solution, which induced tungsten phase detachment and increased the corrosion rate of the W-Cu alloys. While Cl − would accelerate the Cu binder dissolution of W-Cu alloys at high potential during polarization test in strong alkaline solution.